Blood vow [compact disc, unabridged] - Ward, J. R., 1969- (Ward, J. R., 1969- Black dagger legacy., 2016)
The Black Dagger Brotherhood continues to train the best of the best to join them in the deadly battle against the Lessening Society. Among the new recruits, Axe proves to be a cunning and vicious fighter, and also a loner isolated because of personal tragedy. When an aristocratic female needs a bodyguard, Axe takes the job, though he's unprepared for the animal attraction that flares between him and the one he is sworn to protect.